COMMUNITY MIDWIFERY CARE MRS. W EARLY PREGNANCY IN BANGUN REJO VILLAGE REGENCY DELI SERDANG 2026 - Br Tumangger, Dina Sandriana; Ginting, Siska Suci Triana; Sinaga, Rosmani; Marbun, Elpri Rosalita; Bate’e, Cantik Marlin (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: young-age pregnancy remains a global public health concern linked to elevated maternal and infant morbidity and mortality; an initial community assessment in Dusun V, Bangun Rejo Village, identified limited maternal knowledge in managing adolescent pregnancy, contributing to nausea and vomiting that threaten maternal and fetal nutritional status. Objectives: This study aimed to provide comprehensive community midwifery care to Mrs. W, a 21-year-old woman experiencing early pregnancy discomforts, using an analytical observational design with a longitudinal case study approach following Helen Varney’s seven steps of midwifery management. Methods: Care was delivered through four intensive home visits during the field period in Deli Serdang Regency, with data collected via interviews, physical examinations, and SOAP documentation. Results: At baseline, the patient reported frequent morning sickness with vomiting and reduced appetite; midwifery interventions consisted of health education on appropriate pregnancy nutrition, counseling to eat small, frequent meals and avoid known triggers, regular monitoring, and provision of iron and folic acid supplements. Progressive follow-up at each visit included reinforcement of dietary guidance and assessment of symptoms and vital signs. By the fourth visit the patient’s nausea had resolved, appetite normalized, and vital signs remained stable. These findings suggest that. Conclusions: targeted community midwifery care combined with structured education and simple nutritional support can effectively reduce early pregnancy physiological discomforts and help prevent nutritional compromise in young pregnancies.